Guide to ILDJIT - Campanoni, Simone (SpringerBriefs in Computer Science, 2011)
This book is a guide to getting started with ILDJIT, a compilation framework designed to be both easily extensible and easily configurable. Within this framework, it is possible to build a tool-chain by customizing ILDJIT for specific purposes. Customizations can be used within both static and dynamic compilers already included in the framework without adaptations. Moreover, customizations allow modification of both the behaviors and the characteristics of these compilers to better satisfy the particular need. Currently, ILDJIT is able to translate bytecode programs to generate machine code for both Intel x86 and ARM processors. By relying on ILDJIT technology, more input languages or platforms can be supported. After an introduction to ILDJIT, this guide goes into detail on how to exploit it by extending the framework to match specific requirements. Finally, there is an introduction and discussion of the design choices followed during the authors' years of development efforts towards ILDJIT.